2006
DOI: 10.1108/09513550610669167
|View full text |Cite
|
Sign up to set email alerts
|

More (good) leaders for the public sector

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 24 publications
1
36
0
3
Order By: Relevance
“…Others, however, have pointed to the promotion and at least partial adoption of 'transformative' leadership styles (Currie and Lockett, 2007;Lawler, 2007) albeit of 'a rather narrow, managerialist variant' (Currie and Lockett, 2007, p. 341). There are also some voices promoting post-heroic leadership in the public sector as we noted earlier (Alimo-Metcalfe and Alban-Metcalfe, 2006). Yet whether the practice of leadership and management, transactional, transformative or post-heroic, they all seem to be operating in a changing context of circumscribed agency alongside the promotion of forms of surveillance and audit, operationalized through regimes of performativity.…”
Section: Managing To Lead the Public Sectormentioning
confidence: 76%
“…Others, however, have pointed to the promotion and at least partial adoption of 'transformative' leadership styles (Currie and Lockett, 2007;Lawler, 2007) albeit of 'a rather narrow, managerialist variant' (Currie and Lockett, 2007, p. 341). There are also some voices promoting post-heroic leadership in the public sector as we noted earlier (Alimo-Metcalfe and Alban-Metcalfe, 2006). Yet whether the practice of leadership and management, transactional, transformative or post-heroic, they all seem to be operating in a changing context of circumscribed agency alongside the promotion of forms of surveillance and audit, operationalized through regimes of performativity.…”
Section: Managing To Lead the Public Sectormentioning
confidence: 76%
“…Previous research has indicated that despite massive investment by public and private sector organisations in leadership development, most initiatives were regarded as failures (Alimo‐Metcalfe and Alban‐Metcalfe 2000 cited in Alimo‐Metcalfe and Alban‐Metcalfe, ) or partly met the intended objectives (Edmonstone, ). Some of the barriers were that top managers believed that the fact that they occupied the most senior leadership positions was evidence enough that they had ‘what it took’ to be a leader and regarded their development, therefore, as unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…Alimo-Metcalfe (1998), Alban-Metcalfe and Alimo Metcalfe (2000), Alimo-Metcalfe and Alban-Metcalfe (2002a, 2002b called for the analyses of the relationships in the process of leadership and change. Kanungo andMendonca (1996, 2001), Alimo-Metcalfe and Alban-Metcalfe (2006), Aronson (2001), Bass and Steidlmeier (1999), Ciulla (2004b), Kanungo (2001), McAreavey, Alimo-Metcalfe, andConnelly (2001), Trevino (1986), Treviño and Brown (2004), Treviño, Brown, and Hartman (2003), Treviño, Weaver, and Reynolds (2006), and Turner and Müller (2005),undertook vigorous investigations about the relationships between morals, ethics, and values. Investigators Alban-Metcalfe and Alimo-Metcalfe 2000, Alimo-Metcalfe and Alban-Metcalfe (2005b), Aronson (2003, Avolio and Locke (2002), Brown et al(2005), Craig and Gustafson (1998), Garofalo (2003), Gordon and Yukl (2004), Hooijberg and Lane (2005), Ladkin (2006), and Morrison (2001), have performed studies with respect to the relationship between integrity, ethics, and leadership.…”
Section: Discussionmentioning
confidence: 99%